Randomized, controlled trial comparing the retention of a flowable restorative system with a conventional resin sealant: one-year follow up - S. A. M. CORONA, M. C. BORSATTO, L. GARCIA, R. P. RAMOS, & R. G. PALMA-DIBB (Paediatric Dentistry, 2005)
This clinical trial evaluated the retention rate of a flowable restorative system (Bond 1 + Flow-It!) used as a it-and-fissure sealant compared with a conventional filled resin sealant (Fluroshield) over a 1-year period.